Aportes teórico-metodológicos para una etnografía de las audiencias de televisión (trans)nacionales en la Argentina - Balsas, María Soledad (Comparative Cultural Studies: European and Latin American Perspectives, 2017)
This article is based on some methodological considerations related to the conduction of a focus group session with native Italian residents in Buenos Aires, Argentina, in the context of the latest phase of a publicily-funded research project aimed at problematizing the role of (trans)national television in the political engagement of Italian citizens abroad. In spite of the several criticisms that tend to present it in terms of a depoliticizing, easy and quick-result oriented methodological strategy, in this context the focus group technique proved itself to be particularly useful to (re)define daily situation in a political fashion, to address generational gap issues as well as to offer communication opportunities in order to foster a participatory political culture.